Strategi Bersaing PT. Perusahaan Gas Negara (Persero) Tbk SBU Distribusi Wilayah I - Saragih, Jomaren Tuah; Suryadi, Eko (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 8 Nomor 2 Tahun 2014, 2015)
The purpose of thi s research is to analyze competitive strategy implemented by PT Perusahaan Gas Negara (Perser o)  Tbk SBU  Dist ribusi  Wilayah I  to  face competit ion  in downstr eam  natural  gas industry.   Descript ive qualitat ive analysis method  is used by carrying  out SWOT  and V alue  Chain Analysis.   SWOT analysis  is used to  ident ify  and evaluate st r ength, weakness,  opportunity, and threat  of the company,  whereas  the important factors  and  their  r elevance  to  the  futur e  ar e  ident ified  by  V alue  Chain Analysi s.The  r esults  show  that  SBU Wilayah  I  uses  best  price  strategy  and  gives  value  added  cutomer  service  by  maximizing  the  use  of  technology to  create  sustainable  competitive  advantage.
Keywords: natural gas, SBU, SWOT analysis, value chain analysis